1977
DOI: 10.1021/jf60214a040
|View full text |Cite
|
Sign up to set email alerts
|

Volatile flavor constituents of ovine adipose tissue

Abstract: In an effort to enhance the utilization of sheep (Ovis dries) meat, this study was designed to isolate and identify compounds from ovine subcutaneous adipose tissue (Panniculus adiposus) which contribute to the characteristic flavor of the meat. Samples were taken from three Suffolk wether lambs and subsequently steam deodorized, extracted, fractionated, and analyzed. Olfactory and gas chromatographic (GC) analyses confirmed that the bulk of the flavor volatile compounds were in the neutral fraction, some in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 10 publications
(14 reference statements)
2
29
0
Order By: Relevance
“…As expected, many of the compounds identified had been previously described by Caporaso et al (1977), but Nixon et al observed that the formation of aldehydes and ketones comprising the 'muttony' shortlist of Caporaso et al depended on the cooking method. But irrespective of method, the volatiles always smelt 'sheepy' to quote Nixon et al Moreover, Dwivedi (1975) had shown that the 'muttony' volatiles also occurred in beef volatiles.…”
Section: Chemical Components Involved In Sheepmeat Odour and Flavoursupporting
confidence: 52%
See 1 more Smart Citation
“…As expected, many of the compounds identified had been previously described by Caporaso et al (1977), but Nixon et al observed that the formation of aldehydes and ketones comprising the 'muttony' shortlist of Caporaso et al depended on the cooking method. But irrespective of method, the volatiles always smelt 'sheepy' to quote Nixon et al Moreover, Dwivedi (1975) had shown that the 'muttony' volatiles also occurred in beef volatiles.…”
Section: Chemical Components Involved In Sheepmeat Odour and Flavoursupporting
confidence: 52%
“…More recent studies have extended their observations. Caporaso et al (1977) rendered mutton fat (at 50°C) and judged it to have the characteristic odour even after this minimal heating. The rendered fat was then heated to simulate oven temperatures and steam extracted.…”
Section: Chemical Components Involved In Sheepmeat Odour and Flavourmentioning
confidence: 99%
“…Among the compounds mentioned in Table 1, three have been determined as the decisive characteristic flavor compounds of mutton: 4-ethyloctanoic acid (cheese, boiled mutton), 4-methylnonanoic acid (tallow, roasted, mutton), and hexanoic acid (lamb, oily) [6]. Moreover, some aliphatic aldehydes, especially some short-chain aliphatic aldehydes (C 5 -C 9 ), were also reported in sheep meat; these aldehydes are as follows: hexanal (fruity, fatty, and green), heptanal (nutty, oily, and fruity), octanal (fruity, floral, and fatty), nonanal (oily, fatty), and 2-octenal (fruity) [17]. Furthermore, 6-methyl-5-hepten-2-one, 3-methylbutanal, 2-methyl-5-(methylthio) furan, 2-undecenal, and 2,3,5,6-tetramethyl pyrazine were related to emitting meaty odors, and all of these components influence the overall mutton flavor to a certain extent.…”
Section: Standardization Of Chromatographic Fingerprintmentioning
confidence: 99%
“…Noting the importance of fat or adipose tissue in the generation of the characteristic sheepmeat flavor (Hornstein, 1963), F. Caporaso and a team at the Meats Laooratory of The Pennsylvania State University (University Park, Pennsylvania) undertook a study to determine those compounds responsible for the distinctive lamb/mutton flavor. Although the fatty acids, especially the branched chain and unsaturated C S -10 acids, have been identified as flavor constitutents (Wong, 1975), the carbonyls are the most numerous and perhaps the most important of all the various classes of compounds identified in meat flavor studies (Herz, 1970;Caporaso, 1977). Although there are both water-and fat-soluble carbonyls, Sanderson (1966) indicated those involved in meat flavor are primarily lipid-soluble.…”
Section: Sheep 1779 Worldwide Lamb and Sheep Productionmentioning
confidence: 99%